Mysticism and the Atonement: Experiential insights from Evelyn Underhill. (February 2016) - Wrigley-Carr, Robyn
This article brings together two concepts rarely coupled: the doctrine of the Atonement and mysticism. Evelyn Underhill argues they are 'two sides of a greater whole' and that experiential engagement with the relational reality of the Atonement is essential to gain a fuller understanding. Simply engaging intellectually with the Atonement means the richness of the concept is reduced and the mystery is destroyed. The influence of Baron Friedrich von Hügel on Underhill's spiritual formation is described before outlining Underhill's mystical encounters with Christ and her growth in worship. The proper response to the Atonement is not dry, theoretical, lifeless argument, but rather vibrant adoration and wonder. In our fast-paced, contemporary world, the praying theologian who engages experientially with the reality of theological concepts is what is most needed in theological engagement.